Astragalus Polysaccharide RAP Selectively Attenuates Paclitaxel-Induced Cytotoxicity Toward RAW 264.7 Cells by Reversing Cell Cycle Arrest and Apoptosis - Bao, Wan-Rong; Li, Zhi-Peng; Zhang, Quan-Wei; Li, Li-Feng; Liu, Hong-Bing; Ma, Dik-Lung; Leung, Chung-Hang; Lu, Ai-Ping; Bian, Zhao-Xiang; Han, Quan-Bin (Frontiers in Pharmacology, 2019)
Purpose: The purpose of this study was to determine if an Astragalus polysaccharide (RAP) can protect immune cells from the toxic side effects of paclitaxel (Taxol), a powerful anti-tumor drug whose equally powerful side effects limit its clinical use. Methods: We hypothesized that RAP can reduce the toxic effects induced by Taxol. To test this hypothesis, we conducted series studies in vivo and in vitro. First, we confirmed RAP’s effects in vivo utilizing BALB/c mice inoculated with 4T1 mouse breast cancer cells as the tumor model. We injected one group with Taxol and one group with Taxol+ RAP, and recorded differences in the life spans of the mice. Second, a co-culture cell model was used to study the protective effect of RAP on cells vis-a-vis Taxol. The cell cycle and apoptosis of RAW 264.7 cells that were treated with RAP with/without Taxol were checked by flow cytometry and Hoechst staining. Proteins involved in the cell cycle and apoptosis were tested by Western blot to reveal the probable mechanism. Results: RAP prolonged the life span of tumor-bearing mice treated with Taxol. The in vitro experiments showed that Taxol suppressed the proliferation of RAW 264.7 cells and RAP protected the RAW 264.7 cells from Taxol-induced suppression. The protection is selective because RAP had no effect on 4T1 cells. Furthermore, Taxol clearly led to cell cycle arrest mainly at the G2/M phase and generated cytotoxicity against RAW 264.7 cells, while RAP blocked G2/M phase arrest and protected cells from apoptosis. Taxol up-regulated the levels of Caspase-3, P-H2A, PARP, Chk1, p53 and p21 and down-regulated Bcl-Xl and Mcl-1, and RAP reversed the expression of all these proteins. Conclusions: These results suggested that RAP can protect immune cells from Taxol-induced toxicity, by changing the cell cycle and apoptosis.